Portugal : Ex Post Evaluation of Exceptional Access Under the 2011 Extended Arrangement-Press Release; Staff Report; and Authorities Views. (IMF Staff Country Reports; Country Report, 2016)
This paper discusses Portugal's Ex-post Evaluation of Exceptional Access Under the 2011 Extended Arrangement. Portugal faced a sudden stop in financing in 2011. The authorities' IMF-supported program aimed to address the problems that had made Portugal vulnerable to changes in market confidence. The evaluation concurs that the program's 'big decisions' were justified. The main lesson to be drawn from Portugal's experience is that adjustment in the context of currency union membership is difficult. Further work is needed to flesh out the measures required to support internal devaluation and private sector deleveraging. Options for union-level conditionality would benefit from clarification.